2012
DOI: 10.5601/jelem.2009.14.4.787-794
|View full text |Cite
|
Sign up to set email alerts
|

Content of available forms of some micronutrients in soil after long-term differentiated fertilization

Abstract: The objective of this study has been to follow modifications in the content of Cu, Zn and Mn in the topmost layer of soil which had been fertilized for many years with farmyard manure and mineral fertilizers or with mineral fertilizers alone. Soil samples were collected in 2002-2005 from a trial established in 1986 on proper brown podsolic soil, according to the random block design with four replication. The first factor consisted of organic fertilization (manure applied every two years or without manure). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
(10 reference statements)
5
9
0
Order By: Relevance
“…In the case of zinc observed in this study, liming resulted in a decrease of its content, while FYM applications significantly increased the content of this element in soil in relation to the control object. Similar relationships were observed by Sienkiewicz et al (2009). The contents of available boron and molybdenum forms in soil were the lowest in the treatment with exclusive mineral fertilization and they increased both at liming treatments and FYM applications (Table 2).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In the case of zinc observed in this study, liming resulted in a decrease of its content, while FYM applications significantly increased the content of this element in soil in relation to the control object. Similar relationships were observed by Sienkiewicz et al (2009). The contents of available boron and molybdenum forms in soil were the lowest in the treatment with exclusive mineral fertilization and they increased both at liming treatments and FYM applications (Table 2).…”
Section: Resultssupporting
confidence: 77%
“…Fertilization with nitrogen as ammonium form results in soil acidification through nitrification of this ion. Together with increasing soil acidification, an increase is observed of the content of available Cu, Fe, Mn and Zn both in soil and the soil solution (Li et al 2007, Rutkowska et al 2009, Sienkiewicz et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…In the research of Ogiyama et al, the reported concentration of Zn and Cu in an manure-amended arable field ranged from 72 to 170, and 18 to 109 mg kg −1 , respectively [38]. Similar findings were also showed in other published literatures [17,18]. These results indicate the common presence of heavy metal contamination in manure and manure-amended soil environments.…”
Section: Occurrence Of Antibiotics and Heavy Metals In Soils And Manuressupporting
confidence: 89%
“…Mining, processing, and smelting have contaminated soil and water resources throughout the world [13][14][15][16]; the usage of pesticides and mineral elements for animal growth has led to an even wider range of non-point source contamination of heavy metals [17,18]. Unlike antibiotics, metals are not subject to degradation and can represent a long-term selection pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that about half of the world's population suffers from micronutrient shortage makes plant nutrition research indispensable (Cakmak, 2002;Alloway, 2008). Factors influencing the accumulation of micronutrients in plants are related to their concentrations in the soils which control their phytoavailability (Sienkiewicz et al, 2009;Tunçay et al, 2013). Intensive cropping often leads to nutrients' imbalance in soils and may affect nutritional status of plants (Kabata-Pendias, 2001).…”
Section: Introductionmentioning
confidence: 99%